Nilai Pendidikan Aqidah Luqman al-Ḥakim - Maryono Maryono (STAI Ali bin Abi Thalib Surabaya, 2020)
Luqman is a name enshrined in Islam in the Holy Qur'an. His life journey is always wise and above the truth and never leaves him. The story is not only enshrined in the Holy Qur’an, but also enshrined as the name one of the surat’s in the Holy Qur'an. His storie’s have many important education values and very benefits for life. This research is a qualitative study, which uses non-statistical analysis, the data search with the right interpretation to make a systematic description. The Qualitative research is a research that aimed to describe and analyze the phenomena, events, social activities, attitudes, beliefs, perceptions, people's thoughts individual or group. Some descriptions are used to find some principles and explanations that lead to make conclusions. The value of Luqman's aqeedah educations are includes: the obligation to honor of Allah and the prohibition of doing syirik, believing the day of vengeance (the last day) where Allah will repay all of his servants' good or bad actions even though mustard seeds must feel that Allah Subhanahu wa Ta'ala always supervises and know the movements of every human beings, and should not make underestimate the good or bad that is done, however small.